Aaron Boyd's Assignment 8: Difference between revisions

From Class Wiki
Jump to navigation Jump to search
(Created page with 'I decided to use laplace transforms to solve a pendulum equation. A pendulum with a weight of mass m and a massless rod length L is released from an initial angle A<sub>0</sub>. …')
 
No edit summary
Line 1: Line 1:
I decided to use laplace transforms to solve a pendulum equation. A pendulum with a weight of mass m and a massless rod length L is released from an initial angle A<sub>0</sub>. Find a function to determine the angle at any time t.
I decided to use laplace transforms to solve a pendulum equation. A pendulum with a weight of mass m and a massless rod length L is released from an initial angle \theta<sub>0</sub>. Find a function to determine the angle at any time t.
The summation of forces yields
The summation of forces yields
<math>\begin{align}
F_x &= T\sin(\theta)\\
F_y &= T\cos(\theta)-mg = 0
\end{align}</math>



F<sub>x</sub> = T*sin(A)
F<sub>y</sub> = T*cos(A) - mg = 0




Line 13: Line 13:




<math>\begin{align}
F<sub>r</sub> = T- cos(A)*mg = 0
F_r &= T - mg\cos(\theta) = 0\\

F<sub>A</sub> = sin(A)*mg = maL
F_\theta &= \sin(\theta)mg = maL
\end{align}</math>


now since F<sub>r</sub> = 0 we can ignore it and look only at FA.


Since we know F<sub>A</sub> = maL and ma = mLa". We can conclude


<math>\begin{align}
Now since F_r &= 0 we can ignore it and look only at F_\theta.\\
Since we know F_\theta &= maL and ma &= mLa". We can conclude
\end{align}</math>




sin(A)*mg = mLA"
sin(\theta)*mg = mL\theta"




Line 30: Line 31:




A" - sin(A)(g/L) = 0
\theta" - sin(\theta)(g/L) = 0




now we take the laplace transform of this. Unfortunately the laplace transform of that is horrible. Long, complicated, and nearly impossible to solve. So we use the approximation sin(A) = A where A is small.
now we take the laplace transform of this. Unfortunately the laplace transform of that is horrible. Long, complicated, and nearly impossible to solve. So we use the approximation sin(\theta) = \theta where \theta is small.
(I tried to leave sin(A) in the equation. After 4 hours and many wolframalpha.com timeouts I gave up)
(I tried to leave sin(\theta) in the equation. After 4 hours and many wolframalpha.com timeouts I gave up)


with this new equation we get:
with this new equation we get:




g*A(t)/L +s^2*A(t) - s*A(0) - A'(0) = 0
g*\theta(t)/L +s^2*\theta(t) - s*\theta(0) - \theta'(0) = 0


we know that A(0) = A0 and A'(0) = 0
we know that \theta(0) = \theta0 and \theta'(0) = 0




solving for A(t) we get
solving for \theta(t) we get




A(t) = s*A0/((-g/L)+S^2)
\theta(t) = s*\theta<sub>0</sub>/((-g/L)+S^2)




Line 53: Line 54:




A(t) = cosh(t*(g/L)^(1/2))
\theta(t) = cosh(t*(g/L)^(1/2))

Revision as of 11:11, 1 November 2010

I decided to use laplace transforms to solve a pendulum equation. A pendulum with a weight of mass m and a massless rod length L is released from an initial angle \theta0. Find a function to determine the angle at any time t. The summation of forces yields


Polar coordinates may be easier to use, lets try that.

now:



Failed to parse (unknown function "\begin{align}"): {\displaystyle \begin{align} Now since F_r &= 0 we can ignore it and look only at F_\theta.\\ Since we know F_\theta &= maL and ma &= mLa". We can conclude \end{align}}


sin(\theta)*mg = mL\theta"


canceling the common mass term and rearranging a bit we get.


\theta" - sin(\theta)(g/L) = 0


now we take the laplace transform of this. Unfortunately the laplace transform of that is horrible. Long, complicated, and nearly impossible to solve. So we use the approximation sin(\theta) = \theta where \theta is small. (I tried to leave sin(\theta) in the equation. After 4 hours and many wolframalpha.com timeouts I gave up)

with this new equation we get:


g*\theta(t)/L +s^2*\theta(t) - s*\theta(0) - \theta'(0) = 0

we know that \theta(0) = \theta0 and \theta'(0) = 0


solving for \theta(t) we get


\theta(t) = s*\theta0/((-g/L)+S^2)


now we take the inverse laplace transform of that which yields


\theta(t) = cosh(t*(g/L)^(1/2))